THE ANALYSIS OF THE RUSSIAN RAW MATERIALS EXPORTING STRATEGY - N. I. Didenko; D. F. Skripnuk; K. N. Kikkas (Модернизация, инновация, развитие, 2016)
The article gives a methodology for assessing the strategy of export-raw material orientation of the Russian economy, from the point of impact on the social sphere, directly to the person. The dynamics of oil production in Russia, dynamics of export of Russian oil, the price of oil on the world market and the dynamics of the social sphere in Russia were analyzed using data for 1990–2012.The purpose of this article is to study the possibilities of raw material export-oriented strategy of Russia. Possibility raw export-oriented strategy was evaluated dependence of the social sphere - the index GINI, the average wage of household savings from the development of fuel – energy complex. Finding the functional dependence of each of these indicators of social sphere both of oil production and oil exports from Russia plus the price of oil on the world market were tasks.Empirical estimates show the ability of the raw material export-oriented strategy of the Russian economy to ensure the development of the social sphere of the country under condition increasing in the growth rate of energy consumption. Resource-rich countries should pursue a policy of reducing their exports and thus increase their domestic consumption.